2005
DOI: 10.1111/j.1365-2982.2005.00660.x
|View full text |Cite
|
Sign up to set email alerts
|

The external anal sphincter and the role of surface electromyography

Abstract: Assessment of the neuronal control of the external anal sphincter (EAS) has long been restricted to investigating patients with defecation disorders by invasive tools such as needle electromyography (EMG), while less invasive techniques have been regarded as non-suitable for diagnostic purposes. Multichannel surface EMG by means of electrode arrays applied to anal sphincter muscle records and identifies individual motor unit action potentials, their place of origin along the circumference, their repetitive fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 37 publications
1
19
0
1
Order By: Relevance
“…Several motor unit (MU) action potentials (MUAP) traveling across different channels can be identified 13 and the position of the IZ of the identified MUAPs along the circumference can be estimated. [13][14][15] Great attention has recently been devoted to the assessment of the distribution of IZ of EAS (see Digestion, volume 69, 2004 Our method is completely different from other techniques, which do not measure electrophysiological variables, such as the location of the IZ and its asymmetry. It is expected that this totally new information extracted from multi-channel surface EMG can support the development of a technique of clinical relevance.…”
mentioning
confidence: 99%
“…Several motor unit (MU) action potentials (MUAP) traveling across different channels can be identified 13 and the position of the IZ of the identified MUAPs along the circumference can be estimated. [13][14][15] Great attention has recently been devoted to the assessment of the distribution of IZ of EAS (see Digestion, volume 69, 2004 Our method is completely different from other techniques, which do not measure electrophysiological variables, such as the location of the IZ and its asymmetry. It is expected that this totally new information extracted from multi-channel surface EMG can support the development of a technique of clinical relevance.…”
mentioning
confidence: 99%
“…2 mm long, 1 mm diameter) each in a single differential configuration. The use of a multichannel approach allows concomitantly detection of bipolar EMG signals from a number of locations across the muscle . EMG signals were detected up to 1 cm depth.…”
Section: Methodsmentioning
confidence: 99%
“…The conductivity of the mucosa is 1 S/m and the conductivity of the EAS and IAS muscles c d The thickness of the mucosa layer is 1 or 3 mm, in two sets of simulations. The thickness of the IAS is 1 mm (Enck et al, 2005).…”
Section: The Algorithm For the Estimation Of The Distribution Of Izmentioning
confidence: 99%
“…With this technique, it is possible to identify the individual motor unit action potentials (MUAP) in the EMG signal, estimate the position of their IZ along the circumference, and follow the propagation of the action potentials along the muscle fibres (Enck et al, 2004b). Some preliminary studies based on multi-channel detection of surface EMG indicated anatomical differences between genders (Enck et al, 2004b(Enck et al, , 2005, and assessed the correlation between childbirth-related sphincter injuries and faecal incontinence symptoms (Wietek et al, 2007).…”
Section: Introductionmentioning
confidence: 99%